Pengaruh Latihan Metode Drill terhadap Peningkatan Keterampilan Pivot dalam Pertandingan Basket pada Kegiatan Ekstrakurikuler SMA Negeri 1 Kepahiang - Yasir, Muhammad Irfan; Ajayati, Titi; Sumantri, Ajis (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of drill method training on pivot skills in extracurricular basketball activities of students at SMA Negeri 1 Kepahiang. This study used a pre-experimental design with the